PEMANFAATAN TUMBUHAN PEKARANGAN SEBAGAI BAHAN OBAT ALTERNATIF DI DESA JIMBARAN, KECAMATAN KUTA SELATAN, KABUPATEN BADUNG, BALI - Irawati, Irawati; Kriswiyanti, Eniek; Darmadi, A. A. Ketut (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018), 2018)
This study aims to determine types of plants used as alternative medicine, perfect those plants that are mostly used, the processing and used, and diseases that can be treated. Research was carried out on October 2016 until January 2017 from 13 banjar in the Jimbaran village and while the plant identification  as done at the SPT laboratory of Biology Study Program FMIPA Udayana University. The procedure of the study include field observation, interviews followed by sample collected based on purposive sampling and snow ball methods to determine the respondent,  documentation and indetification. The results were obtained 65 species (37 familys) and family of the most widely used was Zingiberaceae. Part of the plant most widely used are leaves (47,1%), followed by rhizomes (12,9%), fruits (11,4%), roots (7,1%), barks (7,1%), flowers (4,3%), seeds (2,9%), saps (2,9%), tubers (2,9%) and aerial roots (1,4%). The processing of medicinal plants is mostly through boiling (44,8%) before drink. Diseases that can be treated were 47 internal diseases and 21 external diseases.